Pelepasan ion nikel dan kromium kawat Australia dan stainless steel dalam saliva buatan (The release of nickel and chromium ions from Australian wire and stainless steel in artificial saliva) - Nolista Indah Rasyid; Pinandi Sri Pudyani; JCP Heryumani (Dental Journal (Majalah Kedokteran Gigi), 2014)
Background: Fixed orthodontic treatment needs several types of wire to produce biomechanical force to move teeth. The use orthodontic wire within the mouth interacts with saliva, causing the release of nickel and chromium ions. Purpose: The study was aimed to examine the effect of immersion time in artificial saliva between special type of Australian wire and stainless steel on the release of nickel and chromium ions. Methods: Thirty special type Australian wires and 30 stainless steel wires were used in this study, each of which weighed 0.12 grams. The wires were immersed for 1, 7, 28, 35, 42, and 49 days in artificial saliva with a normal pH. The release of ions in saliva was examined using Atomic Absorption spectrophotometry. Results: The result indicated that the release of nickel ions on special type of Australian wire was larger than that on stainless steel wire (p<0.005), there were differences in the release of the amount of nickel ions on special type of Australia in different immersion time, and there was a correlation between the types of wire and immersion time. Nickel ions released from the special type of Australian wire detected on the 7th day of immersion and reached its peak on the 35th day, while from stainless steel wire were detected on the 49th day of immersion. The released of chromium ions from the special type of Australian wire and stainless steel wire were not detected until the 49th day of immersion. Conclusion: The release of nickel ions were highest on the 35th day of immersion in special type of Australian wire and they were detected on the 49th day in stainless steel wire. The release of chromium ions were not detected until 49th day of immersion in special type of Australian and stainless steel wire.Latar belakang: Perawatan ortodonti cekat memerlukan beberapa macam kawat untuk menghasilkan kekuatan biomekanika yang sesuai dalam menggerakkan gigi. Pemakaian kawat ortodonti di dalam mulut dapat bereaksi dengan saliva sehingga menyebabkan terjadinya pelepasan ion nikel dan kromium. Tujuan: Penelitian ini bertujuan untuk meneliti pengaruh waktu perendaman dalam saliva buatan terhadap pelepasan ion nikel dan kromium antara kawat Australia tipe spesial dengan kawat stainless steel. Metode: Penelitian ini menggunakan 30 buah kawat Australia tipe spesial dan 30 buah kawat stainless steel dengan berat tiap kawat 0,12 gram. Kawat direndam selama 1, 7, 28, 35, 42 dan 49 hari dalam saliva buatan pH normal. Pemeriksaan pelepasan ion pada saliva menggunakan spektrofotometri serapan Atom. Hasil: Pelepasan ion nikel pada kawat Australia tipe spesial lebih besar dibandingkan dengan kawat stainless steel, terdapat perbedaan pelepasan jumlah ion nikel pada kawat Australia tipe spesial antara waktu perendaman dan terdapat interaksi antara jenis kawat dengan waktu perendaman. Ion nikel yang terlepas pada kawat Australia tipe spesial mulai terdeteksi pada hari ke-7 perendaman dan mencapai jumlah tertinggi pada hari ke-35 sedangkan pada kawat stainless steel mulai terdeteksi pada perendaman hari ke-49. Pelepasan ion kromium pada kawat Australia tipe spesial dan kawat stainless steel tidak terdeteksi sampai perendaman hari ke-49. Simpulan: Pelepasan ion nikel pada kawat Australia tipe special terdeteksi paling tinggi pada lama perendaman hari ke tiga puluh lima, kawat stainless steel terdeteksi pada lama perendaman hari ke empat puluh sembilan. Pelepasan ion kromium pada kawat Australia tipe special dan stainless steel tidak terdeteksi sampai lama perendaman hari ke empat puluh sembilan.